Kekuatan Pembuktian Tanpa Hadirnya Korban Di Persidangan Dalam Perkara Tindak Pidana Pencurian Dengan Kekerasan : Analisis Putusan Pengadilan Negeri Sumbawa Besar Nomor: 142/Pid.B/2023/PN.Sbw - Roli Pebrianto (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This article discusses the importance of witness testimony in the criminal justice process in Indonesia, particularly in cases of violent theft. This research focuses on the decision of the Sumbawa Besar District Court Number: 142/Pid.B/2023/PN.Sbw. The method used is normative legal research, which analyzes primary and secondary legal documents to understand how testimony is used in court despite the absence of the victim. This study finds that witness testimony is crucial in proving criminal acts. However, in this case, most of the testimony provided was testimonium de auditu, based on hearing from others rather than direct experience. This raises issues concerning the validity of such testimony as legitimate evidence. The conclusion of this research indicates that although witness testimony is important, caution must be exercised in assessing its validity, especially when the testimony does not originate from the direct experience of the witness. This is important to ensure a fair trial process in accordance with applicable legal principles.